2014
DOI: 10.7162/s1809-48722010000200011
|View full text |Cite
|
Sign up to set email alerts
|

Audit of Otological Diseases amongst Elderly in Nigeria

Abstract: Summary Introduction:?Aging process is associated with degeneration in different part of the body There is scarcity of literature on the otological diseases in the elderly black African especially Nigerian which is the largest African nation. Thus this study is done with the aim of highlighting the pattern of otological diseases in elderly for careful cost-effective health care plans and to make the aging period more fulfilling and tolerable to the elderly. It is therefore hope that the information will go a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
5
6
2
1
Order By: Relevance
“…As regards the types of ear diseases among the studied elderly, the current study found diminished hearing as the commonest ear problem among the studied population (37%) followed by otitis media (9.4%) and otitis interna (2.9%). These findings are inconsistent with the findings of (1) who reported that the most common ear disease among the studied elderly was aural wax impaction (48.7%) followed by age-related hearing loss (21.4%) and tinnitus (10.5%), and chronic suppurative otitis media was found in 4.6% of the studied participants. Furthermore, in a study conducted by (16), cerumen impaction was the commonest (30.14%) presentation followed by otomycosis externa (27.89%), presbycusis (24.23%) and chronic suppurative otitis media (11.11%), and in a study carried out by (17), chronic suppurative otitis media was the commonest (25%) problem, followed by otomycosis externa (17.5%) and cerumen impaction (15.3%).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As regards the types of ear diseases among the studied elderly, the current study found diminished hearing as the commonest ear problem among the studied population (37%) followed by otitis media (9.4%) and otitis interna (2.9%). These findings are inconsistent with the findings of (1) who reported that the most common ear disease among the studied elderly was aural wax impaction (48.7%) followed by age-related hearing loss (21.4%) and tinnitus (10.5%), and chronic suppurative otitis media was found in 4.6% of the studied participants. Furthermore, in a study conducted by (16), cerumen impaction was the commonest (30.14%) presentation followed by otomycosis externa (27.89%), presbycusis (24.23%) and chronic suppurative otitis media (11.11%), and in a study carried out by (17), chronic suppurative otitis media was the commonest (25%) problem, followed by otomycosis externa (17.5%) and cerumen impaction (15.3%).…”
Section: Discussioncontrasting
confidence: 99%
“…The ear has a complex structure concerned with maintenance of equilibrium as well as hearing. An abnormality or disruption in the anatomical structures and function of the ear can result in ear diseases and may affect all the age groups including the elderly, as a result of aging ( 1 , 2 ). Aging is a natural process that affects all human beings ( 2 ), and different body systems are affected by the aging process at different rates ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found the incidence rate of phonatory disorders to be 29.1%. Kayode et al (2010) in Ilorin, Nigeria, conducted a ten year hospital based retrospective study between January, 1999 and December, 2008 at the ENT Department of University of Ilorin Teaching Hospital, Ilorin. The study included all patients aged 65 years and above who reported to the ENT Clinic (UITH) with ontological complains.…”
Section: Introductionmentioning
confidence: 99%
“…Ao lado destes, diversos estudos tem corroborado com a sua relevância clínica, principalmente quanto a sua prevalência e as consequências em idosos (CRANDEL;ROESE, 1993;NEY, 1993;MOORE et al, 2002;OLOGE 2005;KAYODE et al, 2010). (BARATA, 1998).…”
Section: Introductionunclassified